Early prediction of phenotypic severity in Citrullinemia Type 1. Issue 9 (30th August 2019) - Zielonka, Matthias; Kölker, Stefan; Gleich, Florian; Stützenberger, Nicolas; Nagamani, Sandesh C. S.; Gropman, Andrea L.; Hoffmann, Georg F.; Garbade, Sven F.; Posset, Roland; ,
Abstract: Objective: Citrullinemia type 1 (CTLN1) is an inherited metabolic disease affecting the brain which is detectable by newborn screening. The clinical spectrum is highly variable including individuals with lethal hyperammonemic encephalopathy in the newborn period and individuals with a mild‐to‐moderate or asymptomatic disease course. Since the phenotypic severity has not been predictable early during the disease course so far, we aimed to design a reliable disease prediction model. Methods: We used a newly established mammalian biallelic expression system to determine residual enzymatic activity of argininosuccinate synthetase 1 (ASS1; OMIM #215700) in 71 individuals with CTLN1, representing 48 ASS1 gene variants and 50 different, mostly compound heterozygous combinations in total. Residual enzymatic ASS1 activity was correlated to standardized biochemical and clinical endpoints available from the UCDC and E‐IMD databases. Results: Residual enzymatic ASS1 activity correlates with peak plasma ammonium and L‐citrulline concentrations at initial presentation. Individuals with 8% of residual enzymatic ASS1 activity or less had more frequent and more severe hyperammonemic events and lower cognitive function than those above 8%, highlighting that residual enzymatic ASS1 activity allows reliable severity prediction. Noteworthy, empiric clinical practice of affected individuals is in line with the predicted disease severity supporting the notion of a risk stratification‐based guidance of therapeutic decision‐making based on residual enzymatic ASS1 activity in the future. Interpretation: Residual enzymatic ASS1 activity reliably predicts the phenotypic severity in CTLN1. We propose a new severity‐adjusted classification system for individuals with CTLN1 based on the activity results of the newly established biallelic expression system.